Culture comes first: minorities’ behavior during the Covid-19 pandemic: Arabs and Ultra-Orthodox Jews in Israel - Gadi Hitman (Cogent Arts & Humanities, 2024)
The purpose of this study is to examine minority communities’ behavior and practice in Israel during the Covid-19 pandemic (2020–2021) using Smelser’s model for collective behavior. The paper uses formal documents of Israeli state institutions and media reports and concentrates on two minority groups: Ultra-Orthodox Jews (13% of the population) and Arabs (21%). These two populations constitute minority groups with similarities in aspects such as tradition and language that are unique to each. Both communities also suffered from high morbidity rates compared to the general population. The main conclusions of the study are: (1) Ultra-Orthodox Jews disregarded official decrees and obeyed only the religious leadership; (2) the Arab population distrusted the official establishment and its instructions for two major reasons: longstanding neglect of the health system in Arab localities and frequent policy changes during the pandemic; (3) both groups maintained their patterns of collective behavior despite formal instructions to avoid it during the pandemic; and (4) the state failed to provide both communities with updated information during the pandemic, which increased both groups’ distrust of the formal state instructions. This dysfunctioning was a spark event for further disobeying of both communities.